Bmp signaling exerts opposite effects on cardiac differentiation - De Pater, Emma; Ciampricotti, Metamia; Priller, Florian; Veerkamp, Justus; Strate, Ina; Smith, Kelly; Lagendijk, Anne Karine; Schilling, Thomas F.; Herzog, Wiebke; Abdelilah-Seyfried, Salim; Hammerschmidt, Matthias; Bakkers, Jeroen (Circulation Research, 2012)
RATIONALE: The importance for Bmp signaling during embryonic stem cell differentiation into myocardial cells has been recognized. The question when and where Bmp signaling in vivo regulates myocardial differentiation has remained largely unanswered. OBJECTIVE: To identify when and where Bmp signaling regulates cardiogenic differentiation. METHODS AND RESULTS: Here we have observed that in zebrafish embryos, Bmp signaling is active in cardiac progenitor cells prior to their differentiation into cardiomyocytes. Bmp signaling is continuously required during somitogenesis within the anterior lateral plate mesoderm to induce myocardial differentiation. Surprisingly, Bmp signaling is actively repressed in differentiating myocardial cells. We identified the inhibitory Smad6a, which is expressed in the cardiac tissue, to be required to inhibit Bmp signaling and thereby promote expansion of the ventricular myocardium. CONCLUSION: Bmp signaling exerts opposing effects on myocardial differentiation in the embryo by promoting as well as inhibiting cardiac growth. © 2012 American Heart Association, Inc.
CRIS-Team Scopus Importer:2020-09-23
Keywords: BMP; Bmpr1a; Heart; Smad6; Zebrafish